Comparison of nucleotide sequences of large T1 ribonuclease fragments of 18S ribosomal RNA of rat and chicken. - Fuke, M (1979)
Nucleotide sequences of large T1 ribonuclease fragments of 18S ribosomal RNA of Novikoff rat ascites hepatoma cells and chicken lymphoblastoid cells were determined and compared. Among the 19 large T1 ribonuclease fragments examined of rat 18S ribosomal RNA, 12 fragments were found to be the same in chicken 18S ribosomal RNA. Three fragments of rat 18S ribosomal RNA were not found among large T1 ribonuclease fragments of chicken 18S ribosomal RNA. Four fragments of rat 18S ribosomal RNA were found to be changed in chicken 18S ribosomal RNA. All the changes were point mutations except the change in the largest T1 ribonuclease fragment 1 which is 21 nucleotides long. 2'-0-methylation at the center of the fragment was lost in chicken 18S ribosomal RNA; all the other nucleotides were the same.